Evidence of New States Decaying into Xi(*)(c)pi. - Csorna, SE; Danko, I; McLean, K; Xu, Z; Godang, R; Bonvicini, G; Cinabro, D; Dubrovin, M; McGee, S; Zhou, G; Bornheim, A; Lipeles, E; et al. (2001)
Using 13.7 fb(-1) of data recorded by the CLEO detector at Cornell Electron Storage Ring, we report evidence of two new charmed baryons: one decaying into Xi(0')(c)pi(+) with the subsequent decay Xi(0')(c)-->Xi(0)(c)gamma, and its isospin partner decaying into Xi(+')(c)pi(-) followed by Xi(+')(c)-->Xi(+)(c)gamma. We measure the following mass differences for the two states: M(Xi(0)(c)gammapi(+))-M(Xi(0)(c)) = 318.2+/-1.3+/-2.9 MeV and M(Xi(+)(c)gammapi(-))-M(Xi(+)(c)) = 324.0+/-1.3+/-3.0 MeV. We interpret these new states as the J(P) = 1 / 2(-) Xi(c1) particles, the charmed-strange analogs of the Lambda(+)(c1)(2593).